Linguistic Survey of India (LSI) - Språkbanken Text (University of Gothenburg, 2024)
A digital version of the classic Grierson’s Linguistic Survey of India (LSI; 1903-1927) covering more than 250 varieties representing the four major South Asian language families.

A digital version of the classic Grierson’s Linguistic Survey of India (LSI; 1903-1927) covering more than 250 varieties representing the four major South Asian language families.
Linguistic Survey of India (LSI)
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik